Development of the nursing practice guidelines for prevention of multidrug resistan tuberculosis among hospitalized adult patients in Bangladesh - Mohammad Nurul Anower (Prince of Songkla University, 2014)
Thesis (Ph.D., Nursing)--Prince of Songkla University, 2012